The effectiveness of biology learning media in improving high school students' linguistic intelligence towards biology learning outcomes: A literature review - Salsabila, Adinda Thalia; Rinanda, Adistya Risa; Angeli, Angeli; Putra, M Reyhan Rifky Aditya; Putri, Reta Afita (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
Linguistic intelligence is important in helping students interpret and communicate biological concepts; however, biology learning in schools is still teacher-centered and provides limited verbal stimulation. This study anal yzes the effectiveness of biology learning media in enhancing the linguistic intelligence of senior high school students through a Systematic Literature Review (SLR). From 11,000 initial findings in Google Scholar, the screening process resulted in 10 studies that met the criteria because they explicitly measured indicators of linguistic intelligence. The synthesis shows that differentiated modules, MI-based worksheets, e-learning, Quipper School, videos, 3D animations, and flipbooks consistently produce moderate to high effects. Compared with non-digital media such as printed modules and worksheets, digital media (e-learning modules, Quipper School, 3D animated videos, and flipbooks) show more consistent improvements in linguistic indicators related to verbal reasoning and summarization skills. Overall, media aligned with linguistic aspects effectively enhance conceptual understanding, scientific communication, and biology learning outcomes, while also providing practical guidance for designing language-rich biology instruction.Abstrak. Kecerdasan linguistik penting untuk membantu siswa menafsirkan dan mengkomunikasikan konsep biologi, namun pembelajaran biologi di sekolah masih berpusat pada guru dan kurang memberikan stimulasi verbal. Penelitian ini menganalisis efektivitas media pembelajaran biologi dalam meningkatkan kecerdasan linguistik siswa SMA melalui Systematic Literature Review (SLR). Dari 11.000 temuan awal di Google Scholar, proses penyaringan menghasilkan 10 studi yang memenuhi kriteria karena secara eksplisit mengukur indikator kecerdasan linguistik. Sintesis menunjukkan bahwa modul diferensiasi, LKS berbasis MI, e-learning, Quipper School, video, animasi 3D, dan flipbook konsisten memberikan efek sedang hingga tinggi. Dibandingkan dengan media non-digital seperti modul cetak dan lembar kerja, media digital (modul e-learning, Quipper School, video animasi 3D, dan flipbook) menunjukkan peningkatan yang lebih konsisten dalam indikator linguistik yang terkait dengan kemampuan penalaran verbal dan ringkasan. Secara keseluruhan, media yang selaras dengan aspek linguistik efektif meningkatkan pemahaman konsep, komunikasi ilmiah, dan hasil belajar biologi, serta memberikan panduan praktis untuk merancang pembelajaran biologi yang kaya bahasa.